Proceedings of the Ocean Drilling Program 1990
DOI: 10.2973/odp.proc.sr.112.130.1990
|View full text |Cite
|
Sign up to set email alerts
|

Vein Structures of the Peru Margin, Leg 112

Abstract: Numerous well-developed vein structures occur in Leg 112 cores from the Peru margin. Mud-filled dewatering veins occur in four styles: wide discrete gashes, veins along extensional microfaults, tension-gash arrays, and injections into tension gashes about slump-fold noses. Mud veins occur at shallow depths, less than 10 meters below sea floor (mbsf) in some cases, but some also were recovered as deep as 423 mbsf. Mud vein fill is slightly different in composition than the matrix and consists of a higher propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 20 publications
6
22
0
Order By: Relevance
“…As hitherto known, most of the vein structures in the world are found in the area of trench slope basins or fore-arc basins (e.g. the middle America trench landward slope off Guatemala, the Ogawa & Miyata 1985; the Izu-Bonin trench landward slope off Izu arc, Ogawa et al 1992; the Japan trench landward slope off northern Honshu, Arthur et al 1980, Leggett et al 1987, Knipe 1986; the Peru trench landward slope or basins, , Linsley-Griffin et al 1990). …”
Section: Discussionmentioning
confidence: 97%
“…As hitherto known, most of the vein structures in the world are found in the area of trench slope basins or fore-arc basins (e.g. the middle America trench landward slope off Guatemala, the Ogawa & Miyata 1985; the Izu-Bonin trench landward slope off Izu arc, Ogawa et al 1992; the Japan trench landward slope off northern Honshu, Arthur et al 1980, Leggett et al 1987, Knipe 1986; the Peru trench landward slope or basins, , Linsley-Griffin et al 1990). …”
Section: Discussionmentioning
confidence: 97%
“…Although only few distinct silty to sandy layers have been observed within this sequence, possible mass-wasting activity is indicated by a number of sediment structures, such as inclined beds, contorted beds, and other slumping features. Slumping and sliding also can contribute to vein formation by producing sudden loading and by producing microstructures that localize veins (Lindsley-Griffin et al, 1990). The conspicuous lack of gravel within Unit III may be related to the size of …”
Section: Discussionmentioning
confidence: 99%
“…The origin of vein structures has been discussed by a number of workers, such as Cowan (1982), Ritger (1985), Knipe (1986), andLindsley-Griffin et al (1990), though it is by no means clear that all these workers are dealing with identical structures. The structures from Site 808 are closely similar to those described by Ogawa et al (in press), who suggested that a certain combination of extensional stress, elevated pore pressure, and lithology was required.…”
Section: Other Structuresmentioning
confidence: 99%